2015
DOI: 10.4103/0019-5154.159662
|View full text |Cite
|
Sign up to set email alerts
|

Chediak-higashi syndrome: A case series from Karnataka, India

Abstract: Chediak-Higashi syndrome (CHS) is a rare autosomal recessive disease, characterized by partial oculocutaneous albinism, frequent pyogenic infections, and the presence of abnormal large granules in leukocytes and other granulecontaining cells. The abnormal granules are readily seen in blood and marrow granulocytes. Other clinical features include silvery hair, photophobia, nystagmus and hepatosplenomegaly. However, the presence of abnormal giant intracytoplasmic granules in neutrophils and their precursors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
1
7
0
1
Order By: Relevance
“…The robustness of the adopted procedure was suggested not only by the occurrence, in the BTA14 selection signature, of mostly genes playing a role in pigmentation biology, but also by the fact that two of them, SDCBP and NSMAF, had been previously shown to be knowingly or possibly implicated in hair graying phenotypes, respectively. Indeed, SDCBP (syndecan binding protein) has been identified as one of the dysregulated genes in grey compared to black hair follicles in human premature hair graying patients [41]; NSMAF shares a functional domain with the LYST (lysosomal trafficking regulator) gene, which is mutated in the Chediak-Higashi syndrome (CHS), a rare disorder characterized, among other features, by childhood occurrence of silvery grey colored hair [42][43][44][45][46]. In mice, a mutant LYST allele, named "grey" because of the grey coat color of affected mice, was described by Runkel et al [47].…”
Section: The Multi-cohort F St -Outlier Methods Is a Robust Approach Fmentioning
confidence: 99%
“…The robustness of the adopted procedure was suggested not only by the occurrence, in the BTA14 selection signature, of mostly genes playing a role in pigmentation biology, but also by the fact that two of them, SDCBP and NSMAF, had been previously shown to be knowingly or possibly implicated in hair graying phenotypes, respectively. Indeed, SDCBP (syndecan binding protein) has been identified as one of the dysregulated genes in grey compared to black hair follicles in human premature hair graying patients [41]; NSMAF shares a functional domain with the LYST (lysosomal trafficking regulator) gene, which is mutated in the Chediak-Higashi syndrome (CHS), a rare disorder characterized, among other features, by childhood occurrence of silvery grey colored hair [42][43][44][45][46]. In mice, a mutant LYST allele, named "grey" because of the grey coat color of affected mice, was described by Runkel et al [47].…”
Section: The Multi-cohort F St -Outlier Methods Is a Robust Approach Fmentioning
confidence: 99%
“…CHS is a rare autosomal recessive multisystem disorder of infancy or early childhood, caused by mutations in a single gene-LYST gene localized to 1q42-43. 31 The Hermansky-Pudlak syndrome (HPS) case presented with hypopigmentation of skin and hair, ocular anomalies and easy bruisability. HPS is an autosomal recessive disorder characterized by oculocutaneous albinism, platelet storage-pool deficiency and lysosomal accumulation of ceroid lipofuscin.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic injury occurs with uncontrolled fusion of lysosomes or primary leukocyte granulations and phagocytosis. This event enables the presence of lysosomal inclusion bodies in several cell types 1,24,25 , with the formation of large granules 26,27 and disturbance of lysosomal function 4 .…”
Section: Pathophysiology and Diagnosismentioning
confidence: 99%
“…Source: Adapted from Raghuveer et al 9 The abnormalities that occur in CHS are observed mainly in neutrophils, NK cells, and melanocytes 5 , predominating in the myeloid pathway in relation to the lymphoid pathway, although they are also noticed in lymphocytes, hepatocytes, fibroblasts, renal tubular cells, endothelial cells, hematopoietic cells, platelets, pancreas, and neural and thyroid tissue 4,8,12,16 . These morphological (and consequently metabolic) changes might lead to pancytopenia, neutropenia, reduced hemoglobin levels, coagulogram changes, reduced fibrinogen, and elevated levels of bilirubin, transaminases, triglycerides, ferritin, and C-reactive protein [3][4][5]8,11,24 .…”
Section: Pathophysiology and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation